2023
DOI: 10.3390/jcm12051833
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Elderly Patients Affected by Non-Small Cell Lung Cancer: A Narrative Review

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. Non-small cell lung cancer (NSCLC) accounts for approximately 80% of all lung cancers, and most NSCLC is diagnosed in the advanced stage. The advent of immune check point inhibitors (ICIs) changed the therapeutic scenario both in metastatic disease (in first and subsequent lines) and earlier settings. Comorbidities, reduced organ function, cognitive deterioration, and social impairment give reasons for a greater probability of adverse events,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 188 publications
0
5
0
Order By: Relevance
“…For now, there is no clear definition of an elderly in oncology. In most of the subg analyses of clinical trials, the age of 65 is set as a cut-off to define the elderly popul However, the age of 70 years is used as a cut-off to identify and screen elderly patie the context of geriatric assessment dedicated to older cancer patients [9]. Therefore, i analysis, we used the age of 70 to define the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…For now, there is no clear definition of an elderly in oncology. In most of the subg analyses of clinical trials, the age of 65 is set as a cut-off to define the elderly popul However, the age of 70 years is used as a cut-off to identify and screen elderly patie the context of geriatric assessment dedicated to older cancer patients [9]. Therefore, i analysis, we used the age of 70 to define the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma is a cancer, with 80% of cases diagnosed among patients 70 years or older 26 . Mounting studies distinguish the treatment of cancers between young and elderly people 27 , 28 . Therefore, this study focuses on gut microbiota differences in elderly patients with hepatocellular carcinoma and is the first known gut microbiome study of elderly patients with hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ICIs may not be suitable for lung cancer patients with the above underlying conditions. In addition, the efficacy of ICIs may vary with age, and it has been suggested that the efficacy of ICIs may be reduced in people aged ≥75 years old due to so‐called immunosenescence, a phenomenon which refers to the reduced activity of immunity with older age 28 . Given that there is an increase in comorbidity with increasing age, there may not be a therapeutic indication for ICIs in many elderly patients, thus PEM plus Bev might be a useful regimen for advanced Non‐Sq NSCLC patients who are not fit for chemotherapy with ICIs.…”
Section: Discussionmentioning
confidence: 99%